Primary upper‐limb lymphoedema. (20th November 2012) - Vignes, S.; Arrault, M.; Yannoutsos, A.; Blanchard, M.
<x xml:space="preserve">Abstract</x> Summary Background Lymphoedema is a general term used to designate pathological, regional accumulation of protein‐rich fluid. It can be either primary or secondary, and mainly occurs after cancer treatment. Objectives To analyse the clinical and lymphoscintigraphic characteristics of primary upper‐limb lymphoedema (ULL). Methods All of the patients with ULL were recruited at a single Department of Lymphology between January 2007 and December 2011. Results In total, 60 patients (33 female, 27 male) were enrolled. For the 54 noncongenital lymphoedemas, the mean age at onset was 38·5 (range 3–82) years. Lymphoedema was unilateral in 51 patients (85%). It always affected the hand, and less often the forearm (55%) or upper arm (23%). Eleven patients (18%) developed cellulitis after onset of lymphoedema, and 21 patients (35%) had associated lower‐limb lymphoedema (LLL). Forty‐six patients (with 49 lymphoedematous limbs) underwent lymphoscintigraphy: axillary lymph node uptake was diminished in 18 (37%), absent in 24 (49%) and normal in seven limbs (14%). Among the 43 patients with unilateral lymphoedema and lymphoscintigraphy, 28 had epitrochlear node visualization, suggesting a rerouting through the deep lymphatic system, with 15 only on the lymphoedematous limb and 22 on the contralateral nonlymphoedematous limb. The median follow‐up period was 103 months, and 57/60 patients (95%) considered their lymphoedema to be stable. Conclusions Primary ULL appears later in life than LLL, without predominance in either sex. Infectious complications are rare and patients considered the lymphoedema volume stable throughout life.